Process deviation detection method for dry‐type air‐core reactor based on power factor frequency characteristics - Yonghong Wang; Xingyu Ge; Yu Zhuang; Zihe Meng; Chunming Zhao (IET Science, Measurement & Technology)
Abstract To address the problem that the process deviation of dry‐type air‐core reactors cannot be effectively detected, electrical parameters of reactor are numerically analysed at different frequencies. A new method of process deviation detection by the power factor frequency characteristic is proposed. Considering on‐site power frequency interference, a harmonic analysis method is proposed, which is based on the integer multiple of the power frequency cycle, to calculate the power factor. The results show that the resistance loss remains relatively constant at power frequency and gradually increases at higher frequencies with the number of deviation turns increases. The eddy current loss remains basically unchanged at different turn deviations and frequencies. The change laws of resistance loss and the resistance loss power factor are the same. In a double logarithmic coordinate system, resistance loss power factor changes from linear to non‐linear. The non‐linearity degree can be used to detect the process deviation. The test results are consistent with the theory, and the correctness of the detection method is verified.